AGORAPHOBIA PROBLEM OF ANNA FOX IN THE WOMAN IN THE WINDOW BY A.J. FINN - Suarniti Gusti Ayu Made Rai (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
The title of this scientific writing is Agoraphobia Problem of Anna Fox in The Woman in the Window by A.J. Finn. The aims of this research were to find out the agoraphobia problem experienced by Anna Fox found in the novel and the influences of agoraphobia toward herself and her surroundings. The data are collected by reading the novel repeatedly and using the note-taking technique to find out the statements that related to the topic. Based on the result of the analysis, it is found that Anna Fox’s agoraphobia problem because of Post-Traumatic Stress Disorder (PTSD). The disease influences herself and her surroundings by ruins her body because consuming a lot of drugs, made her lose her job, made her have a bad temperament, depression, and made her insecure.